Pupillometry Assessment of Speech Recognition and Listening Experience in Adult Cochlear Implant Patients - Russo, Francesca Yoshie; Hoen, Michel; Karoui, Chadlia; Demarcy, Thomas; Ardoint, Marine; Tuset, Maria-Pia; De Seta, Daniele; Sterkers, Olivier; Lahlou, Ghizlène; Mosnier, Isabelle (Frontiers in Neuroscience, 2020)
Objective The aim of the present study was to investigate the pupillary response to word identification in cochlear implant (CI) patients. Authors hypothesized that when task difficulty (i.e. addition of background noise) increased, pupil dilation markers such as the peak dilation or the latency of the peak dilation, would increase in CI users, as already observed in normal-hearing and hearing-impaired subjects. Methods Pupillometric measures in ten CI patients were combined to standard speech recognition scores used to evaluate CI outcomes, namely speech audiometry in quiet and in noise at +10 dB signal-to-noise ratio. The main outcome measures of pupillometry were mean pupil dilation, maximal pupil dilation, dilation latency and mean dilation during return to baseline or retention interval. Subjective hearing quality was evaluated by means of one self-reported fatigue questionnaire, and the Speech, Spatial and Qualities (SSQ) of Hearing scale. Results All pupil dilation data were transformed to percent change in event-related pupil dilation (ERPD, %). Analyses show that the peak amplitude for both mean pupil dilation and maximal pupil dilation were higher during the speech-in-noise test. Mean peak dilation was measured at 3.47 +/- 2.29 % noise vs. 2.19 +/- 2.46 in quiet and maximal peak value was detected at 9.17 +/- 3.25 % in noise vs. 8.72 +/- 2.93% in quiet. Concerning the questionnaires, the mean pupil dilation during the retention interval was significantly correlated with the spatial subscale score of the SSQ Hearing scale (r(8) = -.84, p =0023), and with the global score (r(8) = -.78, p=0.0018). Conclusions The analysis of pupillometric traces, obtained during speech audiometry in quiet and in noise in CI users, provided interesting information about the different processes engaged in this task. Pupillometric measures could be indicative of listening difficulty, phoneme intelligibility, and were correlated with general hearing experience as evaluated by the Speech, Spatial and Qualities of Hearing scale. These preliminary results show that pupillometry constitutes a promising tool to improve objective quantification of CI performance in clinical settings.